Panel on quantum computing : physics, math, and computer science. (Manning Publications, 2021)
Quantum computing is a very hot topic, which has a foundation in math like linear algebra. We do know today how to program math like linear algebra in a variety of different software tools, especially those designed to run on GPUs. We use these tools all the time, but are thankfully abstracted away from having to work out the math for each video render by hand each time. What then does it look like to program a quantum computer? What type of math should you know, and when do you need it?.